Chlorine inhalation injury with acute respiratory distress syndrome treated by extra-corporeal membrane oxygenation system - Chen, Te-Fu; Wang, Chih-Hsien; Lain Hermes, Gonzalez; Ko, Wen-Je (Global Journal of Medical and Clinical Case Reports, 2020)
Chlorine inhalation related Acute Respiratory Distress Syndrome (ARDS) is rare in clinical practice. Although full recovery from chlorine inhalation injuries remains the most likely outcome, it is true that permanent disability of lung function or even a fatal outcome are possible in severe cases. Reviewing the literature, there are some reports wherein severely injured cases have a mortal outcome. We report a case of high-dose chlorine inhalation injury which induced ARDS and severe acidosis with refractory shock status 4 hours after the initial insult. A vein to artery Extra-Corporeal Membrane Oxygenation (ECMO) system was applied for the ARDS and systemic steroid therapy was also administered. The patient had a good recovery of the pulmonary oxygenation after 70 hours of ECMO support and intubation and ventilation support for five days. He was then transferred to the ward after a one-week stay in the intensive care unit. Oral steroids were gradually tapered over 4 weeks. The follow-up pulmonary function test, performed 6 weeks after the injury, revealed fair recovery without remarkable sequelae while the high resolution pulmonary computed tomography showed bilateral pulmonary fibrosis. To the best of our knowledge, this is the first case report wherein an ECMO system has succeeded in salvaging a patient who suffered from chlorine inhalation injury complicated with ARDS and refractory shock. It is noteworthy that the ECMO system may be deemed beneficial for this group of patients so long as there is no clinical contraindication for the use of such a therapeutic strategy.